Ionic-Liquid-Based Aqueous Two-Phase Systems Induced by Intra- and Intermolecular Hydrogen Bonds - Wenzhuo Xu; Xinpei Gao; Liqiang Zheng; Fei Lu (Molecules, 2022)
In recent years, aqueous two-phase systems (ATPSs) have been widely used in different fields and have become an increasingly attractive subject due to their application in the separation and purification of biomolecules. In this work, the aqueous phase behavior of ionic liquids (ILs) was modulated by changing the cis-trans structure of the anion in ILs. With the same tetra-butyl-phosphine as the cation, the cis-anion exhibited upper critical solution temperature (UCST) phenomena. In contrast, the trans-anion exhibited lower critical solution temperature (LCST) phenomena. The proposed mechanism shows that the main factors responsible for these phenomena include variations in the dissociation degree with temperature and the steric hindrance of the ILs. This phase behavior combines the chemical equilibrium in a solution with the microstructure of the molecule and is useful for constructing new chemical dynamic equilibria in ATPS. As an example of its application, aqueous solutions of both ILs can be used for the efficient separation and extraction of specific amino acids. The two ATPS systems reported in this work highlight a simple, effective, and environmentally friendly method for separating small biological molecules.